2014
DOI: 10.1016/j.jnucmat.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liquid metal embrittlement susceptibility of oxide dispersion strengthened steel MA956

Abstract: a b s t r a c tThis research examined the susceptibility of MA956 to liquid metal embrittlement using two experimental approaches. In both approaches, historical data on traditional steels was used to determine likely conditions to promote liquid metal embrittlement in lead and lead-bismuth eutectic environments. U-bend specimens of MA956 were found to be immune to liquid metal embrittlement after prolonged exposure to liquid lead. Similarly, slow strain rate testing of MA956 showed immunity to liquid metal em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This explains the greater LME susceptibility of specimens subjected to a pre-exposure treatment or specimens with notches and surface flaws, as compared to those with a smooth surface. In oxygen-rich liquid LBE, failure of the oxide scales also competes with oxide self-healing [460,474,475,502]. Steel tempering at relatively low temperatures can retain more interstitial atoms in the steel matrix, which act as barriers to uniform plastic flow, thereby easing crack initiation in areas of plasticity localisation, and in turn, satisfying the stress threshold criterion mentioned earlier.…”
Section: Crack Initiation Stagementioning
confidence: 99%
See 1 more Smart Citation
“…This explains the greater LME susceptibility of specimens subjected to a pre-exposure treatment or specimens with notches and surface flaws, as compared to those with a smooth surface. In oxygen-rich liquid LBE, failure of the oxide scales also competes with oxide self-healing [460,474,475,502]. Steel tempering at relatively low temperatures can retain more interstitial atoms in the steel matrix, which act as barriers to uniform plastic flow, thereby easing crack initiation in areas of plasticity localisation, and in turn, satisfying the stress threshold criterion mentioned earlier.…”
Section: Crack Initiation Stagementioning
confidence: 99%
“…All these studies demonstrate that once a correct procedure is established to ensure crack initiation, reproducible results can indeed be obtained. It is worthwhile mentioning that the native oxides may not be so fragile, as a couple of studies showed that LME did not occur due to the successful protection by oxides under elastic bending stresses [474,475]. Several studies reporting no LME susceptibility are indicative of the experimental difficulty in achieving wetting or the ability of the native oxides to protect the steel from LME.…”
Section: The Role Of Surface State On Lme Of 9cr Steels (Wettability ...mentioning
confidence: 99%
“…It was concluded that FeCrAl ODS steels (PM2000, MA956) are superiorly resistant to corrosion compared to the FeCrAl ferritic steel (Kanthal-AF) in LBE at higher temperature. Baker and Brewer [77] addressed the issue of LME in MA956 steel. By using slow strain rate tests, they found immunity for this alloy to LME by lead and LBE without control of oxygen at 328 and 150 • C respectively.…”
Section: Aluminum Enriched Materialsmentioning
confidence: 99%
“…The chemical reaction of the material component elements leads to material failure. At the same time, the material embrittlement effect induced by Pb and Bi, namely the embrittlement effect of liquid metal (LME, Liquid Metal Embrittlement [8][9][10]) is also a certain destructive corrosion type.…”
Section: Introductionmentioning
confidence: 99%